2002
DOI: 10.1007/pl00007497
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sequential combined transdermal and oral hormone replacement therapies on serum lipid and lipoproteins in postmenopausal women

Abstract: The aim of this study was to compare the effects of sequential combined transdermal and oral postmenopausal hormone replacement therapies on serum lipid-lipoprotein profiles risk markers for cardiovascular disease. A prospective randomize study was designed: Ninety-six healthy nonhysterectomised postmenopausal women were randomized to receive either transdermal continuous 17beta-estradiol, 0.05 mg/d (Estraderm TTS, Novartis, Basel, Switzerland), with transdermal sequential norethisterone acetate, 0.25 mg/d (Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 38 publications
2
16
1
2
Order By: Relevance
“…An improvement in lipid profi le has been indicated in most of the studies that deal with the effect of HT on lipid metabolism [11,[30][31][32] . There are different effects of HT on lipid-lipoprotein profi les due to routes of administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An improvement in lipid profi le has been indicated in most of the studies that deal with the effect of HT on lipid metabolism [11,[30][31][32] . There are different effects of HT on lipid-lipoprotein profi les due to routes of administration.…”
Section: Discussionmentioning
confidence: 99%
“…There are different effects of HT on lipid-lipoprotein profi les due to routes of administration. Although transdermal estrogen decreases TG levels by avoiding the hepatic fi rst-pass effect [33] , the oral route had a more favorable effect on lipid metabolism than the transdermal route, except TGs [11,34,35] . In this current cross-sectional study, a signifi cantly higher HDL level was observed in intranasal 17 ␤ -estradiol (300 g/day) users with regard to women not on HT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As aforementioned in the Introduction, estrogen receptors have been shown throughout the cardiovascular system including the myocardium [1][2][3][4], and also estrogen has a reducing constrictor effect on the vascular endothelium and improves endothelium-dependent vasodilation in both the peripheral and coronary vasculatures [5][6][7][8][9][10]. The cardioprotective effects of estrogen may not only depend on its beneficial effects on lipoprotein levels, which were well documented [17,24,25], and atherosclerosis, which was induced by estrogen deficiency [26][27][28][29], but also its effects on other aspects of the cardiovascular system. Nevertheless, many questions remain about risk and benefits of estrogen/progestin use in postmenopausal women.…”
Section: Resultsmentioning
confidence: 99%
“…Initiation of the atherogenic response is promoted by hypercholesterolemia because chronic high levels of cholesterol in the bloodstream lead to prolonged retention of low-density lipoproteins in the subendothelial space. 4,5 The renin-angiotensin system (RAS) modulates several components of atherosclerotic process, including inflammation, oxidative stress, and hypertrophy of the vascular wall, 6 and estrogen modulates most of, if not all, the components of the RAS cascade, including the synthesis of angiotensin II (Ang II), the key mediator of the RAS, and the 2 receptor subtypes (AT 1 and AT 2 ) that mediate Ang II action. Both animal 7 and clinical studies 8 demonstrate that estrogen inhibits angiotensin-converting enzyme activity, resulting in decreased levels of Ang II in the circulation and in specific tissues, including the aorta.…”
mentioning
confidence: 99%